Sexual Harassment Without Legal Recourse: The Dilemma Between Culture and Justice - Ahmad Khunaepi; Ahmad Suhendra (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2026)
Sexual harassment refers to any act or behavior of a sexual nature that is carried out without consent and causes discomfort, humiliation, or threat to the victim. The goal of this research is to analyze legal solutions to sexual harassment cases from a social cultural and legal perspective. This study implemented a qualitative descriptive research method using a Systematic Literature Review approach. Researchers collected data by gathering various literature, both from books and scientific articles from national and international journals related to the research objectives. The data analysis used in this study involves evaluating data feasibility. The results show that the presence of the TPKS Law (Law Number 12 of 2022) and the New Criminal Code (Law Number 1 of 2023) plays a very important function in preventing sexual harassment. TPKS Law underscores the importance of integrating legal principles with social values, guaranteeing that statutory provisions are in accordance with human rights standards and gender equality. On the other hand, the Code establishes clearer definitions and broader categories of sexual misconduct, guaranteeing that harassment acts are explicitly acknowledged as criminal offenses. The implementation of the TPKS Law and the New Criminal Code must be firm in the field in protecting victims and providing a deterrent effect on perpetrators of sexual violence crimes. Therefore, there is a need for integration of normative legal and socio-cultural solutions to sexual violence with open public dialogue and cross-sector collaboration among stakeholders.